Enhanced beam characteristics of a discharge-pumped soft-x-ray amplifier by an axial magnetic field - Shlyaptsev, V. N., author; Tomasel, F. G., author; Rocca, Jorge J., author; American Physical Society, publisher (Colorado State University. Libraries, 1996)
We report results of the study of soft-x-ray amplification in a discharge-created plasma under an externally applied axial magnetic field. This technique is observed to improve the uniformity and divergence of the beam of a 46.9-nm discharge-pumped Ne-like Ar soft-x-ray amplifier by decreasing the plasma density gradients at the time of lasing. At the optimum strength of 0.15 T, the magnetic field also causes an increase in the laser beam intensity. At higher fields the Zeeman effect is found to contribute to line broadening, decreasing the laser output.